Pengaruh Media Pembelajaran Informasi dan Komunikasi Teknologi dan Minat Belajar Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS di SMP Negeri 1 Ingin Jaya Kabupaten Aceh Besar - Murdani, Murdani; Sariakin, Sariakin; Mardhatillah, Mardhatillah (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to improve the learning process with a variety of ICT-based media and examine the influence of information and communication technology learning media and learning interest on student learning outcomes in Social Sciences subjects at the Want Jaya 1 State Junior High School, Aceh Besar Regency. This research is a type of survey research with quantitative methods. the results of the research show that: there is an influence of information media and communication technology and interest in learning on student learning outcomes in social sciences subjects at the 1 Want Jaya State Junior High School, Aceh Besar Regency which together have a significant influence, this can be seen from the three variables. has a high influence, namely 34.5 for the learning media variable and 37.9 for the learning interest variable, 0.24, which means the learning media and learning interest variables, and the school environment has an influence of 24.4% on learning outcomes, while the second These variables together have an influence on student results in the Social Sciences subject at Want Jaya State Junior High School 1, amounting to 49.4.